Transcriptomics analysis of gene expression in pulmonary arterial hypertension and identification of hub proteins - Ruhi Hashma, Ruchi Yadav (Journal of Applied Pharmaceutical Science, 2022)
Pulmonary arterial hypertension (PAH) is a disease of increased pressure in blood vessels of lungs which is caused by the blockage in blood vessels. It is a fatal chronic cardiopulmonary disease that affects both heart and lungs. PAH is a common global disease in which irreversible changes in blood vessels, resulting in long-term resistance of blood vessels and right ventricular failure, are caused. In recent decades, tremendous research has been done toward the understanding of basic pathobiology of PAH and its fundamental history, biomarker prognosis, and treatment options. However, studies providing PAH-related transcriptomic experiments and gene expression in PAH condition are rare. To identify the genes involved in PAH microarray, gene expression data was retrieved from NCBI Gene Expression Omnibus database with accession number: GSE113439 includes 15 PAH samples from patients and 11 from normal cell that is taken as controls data. Total of 100 differentially expressed genes (DEGs) were predicted using the Limma package of R and Bioconductor. Functional enrichment of DEGs was done using bioinformatics databases like Gene Ontology used for functional classification of genes and the Kyoto Encyclopedia of Genes and Genomes databases used for pathway study. Interaction Network was modeled using Cytoscape tool and further CytoHubba tool was used for the prediction of hub genes from the network of DEG. Total five genes, i.e., EIF5B, NCL, PNN, RIOK1, and RSL1D1 were identified as hub genes. Correlation analysis of these hub genes shows that they have a function in PAH disease and may involve in the cause and progression of PAH.
Keywords: Differential expression, microarray, network construction, Cytoscape, Affy